RETRACTED: Global Governance V/S COVID-19 Pandemic: A Human Security Approach - Akl, Alain (European Scientific Journal, ESJ, 2021)
A Retraction Notification of the paper Akl, A. (2021). Global Governance V/S COVID-19 Pandemic: A Human Security Approach. European Scientific Journal, ESJ, 17(31), 17. https://doi.org/10.19044/esj.2021.v17n31p17. This paper was submitted on 19.04.2021 to the ESJ special edition PUBLIC POLICIES IN TIMES OF PANDEMICS, edited by Georgios Farantos and Nikitas- Spiros Koutsoukis. After thorough peer review, review by the Special Edition Editors, and corrections from the author, the paper was accepted on 23.06.2021. Subsequently, the author requested a reduction in the publication fee, and the publisher proposed a delay in its payment. The author agreed, and the paper was scheduled for publication. Nonetheless, several days later, the author requested cancellation of the publication. Due to a miscommunication within the ESJ Editorial Office, the paper was published in error. Subsequently, the Editorial Office learned that the paper had been simultaneously submitted to another journal and published. Upon submitting his paper to ESJ, the author signed a statement agreeing not to submit his paper elsewhere while under peer review at ESJ and had not informed the Editorial Office of any other simultaneous submissions. Despite this violation of our submission rules, The Editorial Office takes full responsibility for this retraction and apologizes to the author for the mistaken publication of his paper, which is now retracted. ESJ Editorial Office September 27, 2021